RELATIONSHIP BETWEEN ACADEMIC ANXIETY AND CHEATING BEHAVIOR ON STUDENTS IN SMP N 4 PADANG - Dian Widodo; Alizamar Alizamar (Universitas Negeri Padang, 2019)
This research is motivated by the large number of students who cheat in the high category. Cheating behavior is cheating to get exam answers by justifying any means and getting them through outside information. One factor that is thought to influence is academic anxiety. This study basically aims to: (1) describe student cheating behavior, (2) describe student academic anxiety, and (3) test a significant positive relationship between academic anxiety and cheating behavior on students. This research uses a quantitative method with a descriptive correlational type. The population of this study was 534 students of Padang 4 Junior High School enrolled in the July-December semester of the 2019/2020 school year and a sample of 169 students were selected by Stratified Random Sampling. The instrument used was the Academic Anxiety questionnaire with a reliability of 0.826 and the Cheating Behavior questionnaire with a reliability of 0.914. Data were analyzed with descriptive statistical techniques and Pearson Product Moment techniques with the help of the SPSS program for Windows 20. The findings of the study revealed that: (1) Students' academic anxiety was in the moderate category, (2) Cheating behavior was in the moderate category, (3) and there was a significant positive relationship between acadmic anxiety and cheating behavior in students with a correlation coefficient of 0.938 and a significance level 0,000.